Coping with stress in patients with Multiple Sclerosis - Rzeszutko, Ewa; Rolińska, Agnieszka (Current Problems of Psychiatry, 2011)
Multiple Sclerosis (MS) is a chronic disease of the central nervous system with unclear etiology. It is progressive, has an unpredictable course and is among the most common causes of neurological disability in young and middle-aged adults. The aim of this study is to describe the current studies, which relate to psychological functioning of patients with a diagnosis of MS. This study has showed that MS patients cope differently from normal controls. In addition, patients with MS seem to employ coping strategies that are not optimal for the adaption to their disease. Based on current research, it is difficult to formulate definite conclusions about coping with stress in patients with MS. Future studies are needed to replicate, supplement these findings and should take into account the current methodological limitations.